High-Flow Nasal Cannula untuk Pengelolaan Acute Respiratory Distress Syndrome Akibat COVID-19 - Dimas Hadi Prayoga; Natalia Christin Tiara Revita; Devy Syanindita Roshida; Eska Distia Permatasari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
ARDS or Acute Respiratory Distress Syndrome defines a clinical condition of severe lung disease associated with pneumonia, sepsis and trauma which can be caused by SARS-Cov-2 or COVID-19. COVID-19-induced ARDS has a high mortality rate. The choice of mechanical ventilation is very important so that it can be used as appropriate treatment for ARDS caused by COVID-19, so it is necessary to review journals to obtain information related to preventing an increase in ARDS cases in COVID-19. A search strategy relevant to the study topic was carried out using the databases "Scopus, PubMed, Science Direct, EBSCO and Pro Quest". The keywords used were "ARDS", "HFNC", "NIV", and "Mechanical Ventilation". Full-text articles and abstracts were reviewed to select themes that met the criteria. Articles or journals use randomized controlled trials. Minimum intervention month duration. Or journal articles published from January 2017 to September 2022. Evidence of relative effectiveness was found that HFNC was more effective than NIV. There were seven articles that described HFNC relegating patients to intubation. All articles were analyzed using Randomized Controlled Trials (RCT). Patients treated with HFNC showed better outcomes compared with NIV for COVID-19. Therefore, HFNC should be considered before NIV in COVID-19. However, further research with a larger sample size is still needed to better explain the benefits of HFNC in COVID-19 patients. Keywords: Acute Respiratory Distres Syndrome; COVID-19,  High Flow Nasal Canula; Mechanical Ventilation/ Non Invasive Ventilation